2006
DOI: 10.1111/j.1365-2036.2006.03225.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety of endoscopic sphincterotomy in patients receiving antiplatelet agents – a case–control study

Abstract: SUMMARY ObjectiveTo determine whether antiplatelet agents are associated with endoscopic sphincterotomy-related haemorrhage as few well-controlled data exist on this controversial issue. MethodsA case-control study in a tertiary care setting included cases with bleeding following endoscopic sphincterotomy, matched with 2-3 controls selected according to age AE 15 years, sex, and procedural date AE 2 years. Cases and controls were compared for possible risk factors of postendoscopic sphincterotomy bleeding (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 23 publications
0
55
0
4
Order By: Relevance
“…In addition to these studies, a retrospective study compared 40 patients with post-sphincterotomy bleeding vs 86 matched controls who had no post-sphincterotomy bleeding; similar proportions of patients taking APA were found among both groups of patients (13% aspirin and 3% clopidogrel vs 17% aspirin and 0% clopidogrel in cases vs controls, respectively). 140 Endoscopic sphincterotomy followed by large balloon dilation is increasingly undertaken for large biliary stone extraction; haemorrhage has been reported in 0-8.6% of patients. 141 A single series was identified that included five patients taking aspirin at the time of endoscopic sphincterotomy followed by large balloon dilation; none of them presented with significant bleeding.…”
Section: Ercp On Antithrombotic Therapymentioning
confidence: 99%
“…In addition to these studies, a retrospective study compared 40 patients with post-sphincterotomy bleeding vs 86 matched controls who had no post-sphincterotomy bleeding; similar proportions of patients taking APA were found among both groups of patients (13% aspirin and 3% clopidogrel vs 17% aspirin and 0% clopidogrel in cases vs controls, respectively). 140 Endoscopic sphincterotomy followed by large balloon dilation is increasingly undertaken for large biliary stone extraction; haemorrhage has been reported in 0-8.6% of patients. 141 A single series was identified that included five patients taking aspirin at the time of endoscopic sphincterotomy followed by large balloon dilation; none of them presented with significant bleeding.…”
Section: Ercp On Antithrombotic Therapymentioning
confidence: 99%
“…14 In contrast to the increased risk of bleeding in the setting of transbronchial biopsies under dual antiplatelet therapy as shown by Ernst et al, 11 in our retrospective analysis, ES was performed safely in nine consecutive patients on uninterrupted combined antiplatelet therapy. Neither endoscopically relevant immediate nor clinically significant delayed bleeding was observed.…”
mentioning
confidence: 58%
“…25) Conversely, Hui, et al evaluated the safety of EST with aspirin continuation in a retrospective study. 26) They concluded that aspirin continuation increased the risk of postoperative bleeding even when there was a discontinuation period of one week before EST. Recently, Hamada, et al analyzed a large number of EST and EPBD cases from a nationwide administrative database in Japan and concluded that both procedures could be safely performed in patients receiving antiplatelet agents, although post-procedural bleeding risk might be increased in patients receiving anticoagulants.…”
Section: Endoscopy In Biliary-pancreatic System and Inter-ventionsmentioning
confidence: 99%